Cultural Education based Local Wisdom “Tradisi Tombor Magh” in Fak-Fak West Papua - Ferry Irawan; Dharma Gyta Sari Harahap; Muh. Rafi’y; Minuk Riyana; Cristiana Normalita de lima (Indonesian Journal of Science, Technology and Humanities, 2024)
This article aims to examine one of the strategic efforts to preserve cultural values by orienting on a multicultural approach through cultural education based on local cultural values and principles to instill attitudes that show tolerance and uphold identity as a civilized local community so that The cultural values adhered to remain attached to the younger generation. Based on the results of qualitative phenomenological research and through structured interviews and observations on the indigenous people of Fak-Fak Regency, West Papua, the local wisdom of "Tombor Magh" which is multiethnic and multireligious is able to internalize cultural values ​​​​integratively that reflect the character of tolerant citizens and maintain the integrity of local culture. Local wisdom "Tombor Magh" in addition to functioning to maintain harmony and brotherhood, the basic concept of Tombor Magh functions as the identity of the Fak-Fak community who have a high spirit of tolerance prioritizing the principles of cooperation and togetherness. The orientation of cultural education based on local wisdom is not only obtained in the school environment but the main concept is obtained in the community environment. This can be seen in the existence of the Fak-Fak community which upholds the principle of harmony even though they live in a variety of different